Microwave coagulation therapy for metastatic liver cancer - Sato, Naoki; Hirooka, Yasuaki; Konishi, Ichirou; Suzuki, Kazunori; Yamashiro, Yutaka; Yamaguchi, Yumi; Kaibara, Nobuaki (Journal of Microwave Surgery, 1997)
Microwave coagulation therapy (MCT) was applied to 3 patients with synchronous metastatic liver tumors from colon cancer. After resection of colon cancer, MCT was administered to the liver lesions at 60-90W for 20-90 seconds per bout. We used the monopolar needle electrodes of various length, including an electrode which coagulates the tissue around only the tip. A total of 22 sessions was applied to the 3 tumors. Each patient received intrahepato-arterial chemotherapy after surgery. Abdominal computed tomography showed no blood flow in tumors undergoing MCT. Two of 3 patients are alive without recurrence 17 months highly effective for patients with metastatic liver tumors from colon cancer.